2018
DOI: 10.2147/ppa.s173873
|View full text |Cite
|
Sign up to set email alerts
|

Use patterns of over-the-counter (OTC) medications and perspectives on OTC medications among Korean adult patients with chronic diseases: gender and age differences

Abstract: BackgroundA number of symptomatic patients tend to use over-the-counter (OTC) medications and prescription medications. OTC medications can be easily obtained in pharmacies for self-treatment, but using OTC medications is not always safe and beneficial for patients. The aims of this study were to examine the use patterns of OTC medications and assess patients’ perspectives regarding the use of OTC medications in Korean patients with chronic diseases.Patients and methodsA descriptive, cross-sectional survey was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…As a result, it is critical to assist patients in making use of the information in package leaflets and to improve their understanding. 24 According to the findings, respondents with a higher level of education (bachelor's degree or higher) are more likely to use OTC, which is consistent with the findings of other studies because they can understand and read the descriptions on drug packages. 15,25 In our study, there was no significant association between self-medication and educational level, which is in agreement with the finding of a study conducted in Al Majmaah city.…”
Section: Discussionsupporting
confidence: 87%
“…As a result, it is critical to assist patients in making use of the information in package leaflets and to improve their understanding. 24 According to the findings, respondents with a higher level of education (bachelor's degree or higher) are more likely to use OTC, which is consistent with the findings of other studies because they can understand and read the descriptions on drug packages. 15,25 In our study, there was no significant association between self-medication and educational level, which is in agreement with the finding of a study conducted in Al Majmaah city.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, a pharmacist’s intervention, for instance, as a follow up program or identification of OTC drug misuse and abuse, can lead to improved patient outcomes [24, 25]. Several studies concluded that the role of pharmacists in educating consumer of appropriate use of OTC drugs is essential for appropriate use [2629]. However, the need for improvement of OTC consultation in the pharmacy setting has been recognized [2931].…”
Section: Discussionmentioning
confidence: 99%
“…OTC medications are not always considered safe and beneficial for patients as they can be exposed to unexpected adverse drug reactions and drug-drug and drug-food interactions. 6 OTC drugs can also have potential for their misuse and abuse such as codeinebased medicines, cold and cough medications, sedative antihistamines, decongestants and laxatives. 7 The dangers of self-medication are often underestimated, particularly with OTC drugs.…”
Section: Discussionmentioning
confidence: 99%